Percutaneous Nephrolithotomy in Patients With Solitary Kidney - Mohammad Hadi Shakibi (Urology Journal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate percutaneous nephrolithotomy (PCNL) in the patients with solitary kidneys. Materials and Methods: Between 1995 and 2005, we had 11 patients with a solitary kidney and kidney calculi who underwent PCNL at our center. Tubeless and standard PCNLs were performed in 3 and 7 patients. In 1 patient, we could not achieve access to the system due to the stricture of the infundibulum. Results: The calculi were extracted or fragmented successfully in 10 patients. In 2 patients with residual calculi, a double-J catheter was inserted and extracorporeal shock wave lithotripsy (SWL) was performed. Retroperitoneal hematoma was detected in 3 cases by ultrasonography 1 week after the procedure, which was treated conservatively. Also, fever occurred in 3 patients after the procedure which was treated successfully. The patients were discharged on the 3rd and 4th postoperative days. Conclusion: Although PCNL is accompanied by the risk of complications such as severe bleeding that may result in kidney loss in patients with a solitary kidney, the rate of success and complications seem to be similar to the other patients if careful operation and correct selection of candidates are done. Therefore, we recommend cautious performance of PCNL in patients with solitary kidneys.